PENINGKATAN KINERJA PENGELOLAAN KAS UMKM SHUTLLECOCK MELALUI IMPLEMENTASI SISTEM INFORMASI KAS (SI-KAS) - Widianto, Andri; Faedah, Yusri Anis; Mahmudah, Nurul; Fuadha, Shafa (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The invested capital is not managed correctly, so the recording of business and personal finances is still mixed. The Cash Information System (Si-Kas) is an information system created to facilitate users in recording finances, both cash receipts and expenditures. This community service method uses the Si-Kas direct practice method. This community service activity concludes that the shuttlecock UMKM will use the Si-Kas application to increase work effectiveness and efficiency.